Distribution of hospital care among pediatric and young adult Hodgkin lymphoma survivors—A population‐based cohort study from Sweden and Denmark - Glimelius, Ingrid (Cancer Med, 2019)
The burden of late effects among Hodgkin lymphoma (HL) survivors treated according to contemporary protocols remains poorly characterized. We used nation‐wide registers to assess number of inpatient bed‐days and specialist outpatient visits among 1048 HL‐patients (<25 years, diagnosed 1990‐2010) and 5175 country‐, sex‐, and age‐matched comparators. We followed them for up to 24 years, with time‐dependent assessment of relapse status. International Classification of Diseases (ICD‐10) chapter‐specific hazard ratios (HRs) were assessed in Cox regression analyses, and nonparametric statistics described patterns of health‐care‐use. Relative to comparators, relapse‐free survivors were at increased risk of infections, diseases of the blood, endocrine, circulatory and respiratory systems, and unspecific symptoms, HRs ranging from 1.86 to 3.05. Relative to comparators, relapsed survivors had at statistically significantly increased risk of diseases reflecting practically all investigated disease‐chapters, HRs ranging from 1.60 to 18.7. Among relapse‐free survivors, 10% of the patients accounted for 80% of all hospital bed days, and 55% were never hospitalized during follow‐up. Among relapsed‐survivors, 10% of the patients accounted for 50% of the bed days, and only 24% were never hospitalized during follow‐up. In contrast, 10% of the comparators accounted for 90% of hospital bed days and 75% were never hospitalized. These findings challenge the impression of a uniformly distributed long‐term morbidity among all HL survivors and emphasize the need for early identification and attention to patients particularly susceptible to late effects, such as relapsed survivors.